Análisis de contratos y metodología de valoración (pricing) de opciones plan vanilla, con subyacente precio Spot del mercado eléctrico colombiano (2017)
The incorporation of derivative instruments into the electricity market in Colombia allows this to be more liquid, in addition it would allow great flexibility to the agents to adjust their desired hedges with the instruments available in that market, the Colombian market only has a financial market of energy futures Which is in development. Looking at previous work, we found previous developments that demonstrate how a reduced amount of plain vanilla derivatives, if offered by the market, can meet the market coverage needs of any market participant, to evaluate the actual incorporation of these alternatives into market, isnecessary an appropriate valuation of the instruments to be offered in the market, traditional methodologies such as the Black-Sholes formula for example, do not allow direct application for the particularities of the commodity kWh, as its non-storability, for example, Obeys to a geometric Brownian movement, therefore we searched for methodologies more in line with these needs...